Antibacterial Activity of Hermetia illucens (Black Soldier Fly) Maggot Extract Against Salmonella typhi - Andrianto, Dimas; Hasim; Muhammad, Zulfikar; Dwicesaria, Maheswari Alfira (Current Biochemistry, 2025)
Typhus is an acute fever caused by Salmonella typhi bacterial infection. This research aims to test the efficacy of BSF maggot extract as an antibacterial against Escherichia coli and Salmonella typhi. The stages in this research are the preparation of maggot samples, determination of water content of samples, extraction of maggot BSF, screening of antibacterial activity of maggot BSF against Escherichia coli and Salmonella typhi, fractionation from the best results of antibacterial activity of maggot extract BSF and the test of antibacterial activity of maggot BSF fraction against Escherichia coli and Salmonella typhi, fractionation of the best results of antibacterial activity of maggot extract BSF and the test of antibacterial activity of maggot BSF fraction against Escherichia coli and Salmonella typhi. Extraction was carried out by a multi-level maceration method using acetone, methanol and water solvents, then the extract was tested for antibacterial activity against Salmonella typhi using the disc diffusion method with the best results, acetone extract with an inhibition zone of 8.13 mm ± 0.153. Then, acetone extract was fractionated according to its polarity, namely n-hexane, dichloromethane, ethyl acetate, and water. The results of the fractionation were tested for antibacterial activity against Escherichia coli and Salmonella typhi using the disc method with the best fraction was the n-hexane fraction, at a concentration of 2500 ppm with inhibition zones 8.37 mm ± 0.32 (Escherichia coli) and 9.00 mm ± 0.00 (Salmonella typhi)